Wpływ czasoprzestrzennej zmienności opadu na odpływ kanalizacją ogólnospławną na przykładzie miasta Nowa Sól = Impact of spacetime variability on drainage via combined sewage systems on the example of the town of Nowa Sól - Nowogoński, Ireneusz; Bartos, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article have been presented issues related to the phenomenon of rainfall-runoff. As additional factors affecting the results of the simulation were identified: the speed and direction of movement of precipitation in the ratio of the catchment. The results obtained for the actual catchment area have been compared with the results of model simulations in the catchments. Calculations were performed using Epa SWMM 5.0.
Keywords: kanalizacja deszczowa; modele symulacyjne; storm water drainage; simulation models